Topological electronics - Matthew J. Gilbert (Nature Portfolio, 2021)
Topological materials are extensively studied in condensed matter physics and several have been studied to the point where it is now time to ask if these unique materials have a role to play in next generation technologies. The author reviews the current status of well-characterized topological materials such as Bi2Se3 for electronic device applications, focusing on selected technological aspects and their promise for engineering applications.